Phytomanagement of fly ash - Pandey, Vimal Chandra (Elsevier, 2020)
Phytomanagement of Fly Ash brings together the recent and established knowledge of different aspects of fly ash management, providing a cutting-edge synthesis of scientific and experiential knowledge on contaminated site restoration. Phytomanagement of Fly Ash provides readers with ecologically friendly and cost-effective solutions to decontaminate fly ash polluted sites, along with potential opportunities in phytoremediation that also yield biodiesel, aromatic oil, bio-fortified products and pulp-paper biomass. The book also focuses on novel topics, such as afforestation on fly ash catena, adaptive management, potential sink for carbon sequestration, and ecosystem goods and services. This book is a useful reference for environmental professionals in the coal industry, ecological planners and managers, students, practitioners and policymakers involved in phytoremediation. --